Traditional Dance Improves the Physical Fitness and Well-Being of the Elderly - Douka, Styliani; Zilidou, Vasiliki I.; Lilou, Olympia; Manou, Vasiliki (Frontiers in Aging Neuroscience, 2019)
Regular physical activity is considered one of the most important factors for lifestyle, for maintaining good health in older ages and increasing life expectancy. Dance is considered an activity that involves coordinating movements with music, as well as brain activation because it is constantly necessary to learn and remember new steps. Dance as a musical-kinetics skill, requires the coordination of body movements with rhythmic stimuli, developing the adaptability of the movement. One hundred thirty (130) elderly people aged 60 years and over (mean age 67 years old) with an average of 8 years of education, attended Greek traditional dance sessions for 32 weeks. The frequency was 2 times per week, for 75 minutes per session. Dances were selected from all over Greece with moderate intensity initially. During the program, they had the opportunity to try with greater intensity dances. At the beginning and after the end of intervention all the participants were evaluated by the Fullerton Senior Fitness Test for their physical fitness, the Single Leg Balance and the Handgrip Strength Test. The results showed a significant improvement in their physical fitness (Chair Stand: T=-5.459, p<0.001; Arm Curl: T=-5.750, p<0.001; Back Scratch: T=-4.648, p<0.001; Sit and Reach: T=-4.759, p<0.001; Two Min Step: T=-5.567, p<0.001; Foot Up and Go: T=-8.599, p<0.001) and at their static balance with eyes open (Balance 1 leg: T=-4.996, p<0.001) and Handgrip Strength (Handgrip: T=-3.490, p<0.001). Elderly seem to enjoy dancing as an activity, while maintaining their functionality. Probably elderly in traditional dance cause prosperity in their lives by promoting active aging.